(untitled) (Forum Theologicum Sardicense, 2025)
Kostadin Nushev, Orthodox Perspectives of Theological Dialogue and Christian Unity according to Nikolai Glubokovsky After establishing himself in Bulgaria in the early 1920s and beginning his academic and scientific work at the Theological Faculty of Sofia University, Professor Glubokovsky continued to actively research Orthodox theology and science. He also participated, along with other prominent Russian church clergy and theologians, in numerous international scientific and religious forums. Some of these forums were dedicated to Christian theological dialogue and various issues related to the relationships between the Orthodox Church and Western Christian denominations. During this period, Professor Glubokovsky participated more actively, consciously, and confidently in international initiatives and conferences focused on theological dialogue with the Anglican and Old Catholic Churches. He attended these forums both as a representative of the Bulgarian theological and academic community and as an official delegate of the Bulgarian Orthodox Church, as well as a representative of the Russian Orthodox Church and the Russian academic community in Europe. The main purpose of this publication is to provide a brief commentary on some of the theological arguments presented by Professor Glubokovsky during these dialogues in 1925 in London. His theological presentations were published under the broad title “Christian Unity and Enlightenment in the Orthodox Theological Perspective.” The publication includes two separate lectures delivered by Professor Glubokovsky in English, respectively at London University and King’s College, London. According to Professor Glubokovsky, the issues of Christian unity, or „ecumenical unity,“ are among the most important of the time. These issues should be considered in light of Biblical and Patristic truths, which are universally important to Orthodoxy and considered “generally accepted axioms” by the higher church hierarchy, theologians, and ordinary Christians.